Assessing the effect of an online HIV/AIDS course on 1styear pharmacy students’ knowledge - Fatima Suleman (South African Medical Association, 2016)
Background. More international HIV/AIDS intervention initiatives targeting young adults are needed to help reach targets set by the Joint United Nations Programme on HIV and AIDS (UNAIDS). Objectives. To determine the effect of an online HIV/AIDS course on 1st-year pharmacy students’ knowledge of HIV prevention and transmission and of the science of HIV infection. Methods. Online anonymous surveys, the Pre- and Post-Confirmation of Acceptance for Studies, were administered by means of an online survey tool, SurveyMonkey (USA), to 1st-year pharmacy students, from 2009 to 2013. These surveys were administered online during the first and last weeks of class, respectively. Results. With regard to HIV prevention and transmission, student knowledge of the manner in which HIV is transmitted improved during the course. Overall, students were more confident about their knowledge of HIV prevention. They also indicated that as a direct result of taking the AIDS Online International course they were more reluctant to have unsafe sex and more confident about how to protect themselves against HIV/AIDS. Their scientific knowledge also improved. Conclusion. The implementation of an online HIV/AIDS course has proved to be an effective method of HIV/AIDS education, and may also be a viable HIV intervention initiative.